Vertical growth control during maxillary expansion using a bonded Hyrax appliance - Francisco Marcelo Paranhos Pinto; Luciana Baptista Pereira Abi-Ramia; Andrea Sasso Stuani; Maria Bernadete Sasso Stuani; Flavia Artese (Dental Press Editora, 2012)
INTRODUCTION: Rapid maxillary expansion (RME) for the treatment of maxillary deficiency and posterior crossbite may induce changes in the vertical dimension. Expanders with occlusal splints have been developed to minimize unwanted vertical effects. OBJECTIVE: This preliminary study used cephalometri radiographs to evaluate the vertical effects of RME using a Hyrax appliance in children with maxillary deficiency. METHOD: Twenty-six patients (11 boys; mean age = 8 years and 5 months) with maxillary deficiency and posterior crossbite were treated using a Hyrax appliance with an acrylic occlusal splint. Radiographs and cephalometric studies were performed before the beginning of the treatment (T1) and after RME active time (T2), at a mean interval of 7 months. Results were compared with normative values. RESULTS AND CONCLUSIONS: At the end of treatment, there were no statistically significant changes, and measurements were similar to the normative values. Data showed that there were no significant effects on vertical growth, which suggests that appliances with occlusal splints may be used to correct transverse deficiencies regardless of the patient's growth pattern.